A ADVANTAGES AND DISADVANTAGES OF USING DIGITAL TECHNOLOGIES IN LEARNING ENGLISH: ADVANTAGES AND DISADVANTAGES OF USING DIGITAL TECHNOLOGIES IN LEARNING ENGLISH - Tursunova, Tursunova (Журнал иностранных языков и лингвистики, 2022)
The term “Digital technology” is a pretty broad term, and considering nearly everything today relies on computers in one way or another it covers a lot of things.